Chaperone-mediated autophagy regulates proliferation by targeting RND3 in gastric cancer. Issue 3 (3rd March 2016) - Zhou, Jinfeng; Yang, Jianjun; Fan, Xing; Hu, Sijun; Zhou, Fenli; Dong, Jiaqiang; Zhang, Song; Shang, Yulong; Jiang, Xiaoming; Guo, Hao; Chen, Ning; Xiao, Xiao; et al.
ABSTRACT: LAMP2A is the key protein of chaperone-mediated autophagy (CMA), downregulation of LAMP2A leads to CMA blockade. CMA activation has been implicated in cancer growth, but the exact mechanisms are unclear. Elevated expression of LAMP2A was found in 8 kinds of tumors (n=747), suggesting that LAMP2A may have an important role in cancer progression. Unsurprisingly, LAMP2A knockdown in gastric cancer (GC) cells hindered proliferation, accompanied with altered expression of cell cycle-related proteins and accumulation of RND3/RhoE. Interactomic and KEGG analysis revealed that RND3 was a putative CMA substrate. Further study demonstrated that RND3 silencing could partly rescue the proliferation arrest induced by LAMP2A knockdown; RND3 was increased upon lysosome inhibition via both chemicals and LAMP2A -shRNA; Furthermore, RND3 could interact with CMA components HSPA8 and LAMP2A, and be engulfed by isolated lysosomes. Thus, constant degradation of RND3 by CMA is required to sustain rapid proliferation of GC cells. At last, the clinical significance of LAMP2A was explored in 593 gastric noncancerous lesions and 173 GC tissues, the results revealed that LAMP2A is a promising biomarker for GC early warning and prognosis of female GC patients.